Kosakata Serapan dalam Bahasa Arab pada Buku Al-‘Arabiyyah Bayna Yadayk : Kajian Linguistik Kontemporer - Khojijah Salsabela; Ainur Rofiq Sofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Loanwords are a linguistic phenomenon that reflects the dynamic nature of a language in its interaction with other languages. Arabic, as a language with a long-standing history in world civilization, has undergone processes of lexical borrowing from various foreign languages—phonologically, morphologically, and semantically. This study aims to identify and analyze the forms of loanwords found in the book Al-‘Arabiyyah Bayna Yadayk, one of the most widely used Arabic language textbooks internationally, including in Indonesia. The method employed is descriptive qualitative with a contemporary linguistic approach. The findings indicate that the textbook contains numerous loanwords from languages such as English, French, Turkish, and Persian. These borrowed terms have undergone phonological and morphological adaptations to fit the structure of Arabic. This study reveals that the use of loanwords in Arabic language learning materials not only enriches the vocabulary but also reflects the openness of the Arabic language to global developments.